Yield and quality responses of hybrimas sweet corn to different combination of organic and inorganic fertilizers - Mohamad, Muzhafar (2015)
Zea mays or locally known as corn is the third most important crop in the world production cereal crops. In Malaysia, sweet corn production is insufficient to meet the domestic demand. In order to help the farmer to increase the corn production in Malaysia, this experiment was conducted to determine the suitable proportion of organic and inorganic fertilizers for sweet corn for growth and yield production of sweet corn. This experiment was conducted at Ladang 10, University Putra Malaysia. The experimental design used was Randomize Completely Block Design (RCBD) with five treatments and each treatment consists of eight replications of corn tree. The treatment were 100% organic fertilizers (T1), 70% organic fertilizers and 30% inorganic fertilizers (T2), 50% organic fertilizers and 50% inorganic fertilizers (T3), 30% organic fertilizers and 70% inorganic fertilizers (T4) and 100% inorganic fertilizers (T5). Split fertilized application was done before planting and on 30 and 35 days after planting for inorganic fertilizers and organic fertilizers respectively. The parameters that measured in this experiment were plant height, number of leaves, leaves size, day of flowering, day of tasseling, wet weight of corn with husk, dry weight of corn with husk and dry weight of corn without husk.